Globalisasi sebagai Ancaman Non-Tradisional: Erosi Identitas Budaya dan Sejarah Nasional Indonesia di Era Digital - Zaky Ruzbihan (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2026)
The phenomenon of globalization is rapidly expanding and influencing nearly every aspect of life. Foreign cultures are entering Indonesia through various digital platforms. If left unchecked, these external cultural influences could erode the nation’s identity and history. This study examines how cultural heritage and national history are increasingly being eroded by globalization, with a primary focus on the role of the digital age as a catalyst for this acceleration. The researcher employed a literature review method using a qualitative-descriptive approach. The results of the analysis are clear: the erosion of Indonesia’s cultural identity has been categorized as a non-traditional threat. This is multidimensional, transcends national borders, involves global digital corporations, and is now recognized as a threat to national security. Social media and digital platform algorithms accelerate this process, particularly among Gen Z. Ali Khamenei’s thoughts on cultural warfare are highly relevant for understanding the current situation. The impacts span numerous aspects from social stability, ideology, and the economy to politics and defense. The researchers recommend that the government strengthen cross-sectoral coordination, expand the BPIP and DPPI programs into the digital realm, revitalize cultural and history curricula, and promote local culture through more innovative methods on digital platforms.